2010
DOI: 10.1016/j.crohns.2010.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the measurement of azathioprine metabolites in the assessment of non-adherence

Abstract: Azathioprine is a thiopurine immunosuppressive antimetabolite used to chronically treat inflammatory bowel disease and autoimmune hepatitis. Azathioprine treatment is a long-term therapy and therefore it is at risk for non-adherence, which is considered an important determinant of treatment inefficacy. Measurement of 6-thioguanine and 6-methylmercaptopurine nucleotides has been recently suggested as a screener for non-adherence detection. We describe four young patients in which non-adherence to azathioprine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…This is especially relevant in those non-responding patients: low levels of 6TGN and 6MMP may lead to strength measures to improve adherence or to increase the dose of thiopurines. Moreover, some evidence suggests that medical supervision based on the routine determination of thiopurine metabolites may improve adherence to therapy, and therefore result in better outcomes 59 60…”
Section: Monitoring Thiopurine Metabolitesmentioning
confidence: 99%
“…This is especially relevant in those non-responding patients: low levels of 6TGN and 6MMP may lead to strength measures to improve adherence or to increase the dose of thiopurines. Moreover, some evidence suggests that medical supervision based on the routine determination of thiopurine metabolites may improve adherence to therapy, and therefore result in better outcomes 59 60…”
Section: Monitoring Thiopurine Metabolitesmentioning
confidence: 99%
“…Such an approach also facilitates determination of adherence to therapy . Identification and subsequent counseling of patients who are non‐adherent was shown by Stocco et al . to have positive outcomes, as reiterated in the recent HCQ in lupus studies …”
Section: Azathioprinementioning
confidence: 98%
“…showed that measurement of metabolites and use of a metabolite‐dosing algorithm facilitated appropriate dosing decisions, with 24% avoiding inappropriate dose escalation, and 87% of patients achieving better clinical outcomes . Such an approach also facilitates determination of adherence to therapy . Identification and subsequent counseling of patients who are non‐adherent was shown by Stocco et al .…”
Section: Azathioprinementioning
confidence: 99%
“…Treatment of IBD with thiopurines is a long-term therapy and therefore it is at risk for non-adherence, which is considered an important determinant of treatment inefficacy, even in pediatric patients; the additional level of medical supervision given by this assay has been reported to improve adherence to medical treatment and consequently the response to therapy [78,79].…”
Section: Pharmacokinetic Assays For Thiopurines: Measurement Of Azathmentioning
confidence: 99%